Identification and Characterization of a Germline Mutation in CARD11 From a Chinese Case of B Cell Expansion With NF-κB and T Cell Anergy - Zhao, Peiwei; Meng, Qingjie; Huang, Yufeng; Zhang, Lei; Luo, Sukun; Zhang, Xiankai; Tan, Li; Zhou, Aifen; Xiong, Hao; He, Xuelian (Frontiers in Immunology, 2021)
B cell expansion with NF-κB and T cell anergy (BENTA) is a rare primary immunodeficiency disorder caused by gain-of-function (GOF) mutations in the CARD11 gene. Affected patients present with persistent B cell lymphocytosis in early childhood paired with lymphadenopathy and splenomegaly. Until now only six activating mutations from 14 patients have been reported in CARD11. Here we report a patient from China with polyclonal B cell lymphocytosis and frequent infections in early life. A heterozygous mutation (c.377G>A, G126D) in exon 5 of CARD11 gene (NM_032415) was identified by whole exome sequencing. In vitro functional studies showed that the G126D mutation is associated with increased expression of CARD11 and NF-κB activation in Hela cells. Flow cytometry analysis indicated NK cell activity and CD107a degranulation of the patient were decreased. RNA sequencing analysis showed that a number of genes in NF-κB pathway increased while those involved in NK cell activity and degranulation were down-regulated. In summary, our work identified a de novo germline GOF mutation in CARD11 with functional evidence of pathogencity towards BENTA.